THE RATE OF SEDIMENTATION ESTIMATION OF TANJUNG API-API ESTUARY SOUTH SUMATERA BY USING 210Pb PROFILE - Purnomo Raharjo (Marine Geological Institute of Indonesia, 2010)
Sedimentary processes occur intensively in Tanjung Api-Api area situated in the estuary of Musi Banyuasin river. A study on 210Pb isotopes of the sediments has been done to understand the rate of sedimentation. For that purpose, the Marine Geological Institute of Indonesia (MGI) has also conducted bathymetry and sediment distribution mappings. Two samples represent depths of 17-30 cm and 190-210 cm below sea floor give age of 11.54 and 22.45 years. The average of sedimentation rate is 2.03 cm/years (from 0 to 0.3 m below seafloor) and 8.9 cm/years (until 2.1 m depth below seafloor). The result shows, decreasing sedimentation rate upward, that indicates the surficial sediment less influenced by wave and surface current nowadays. Keywords : 210Pb isotope, rate sedimentation, Tanjung Api-Api Proses sedimentasi yang intensif terjadi di kawasan Tanjung Api-Api yang terletak di muara Sungai Banyuasin. Penelitian isotop sedimen 210Pb untuk mengetahui kecepatan sedimentasi telah dilakukan oleh Puslitbang Geologi Kelautan, selain itu dilakukan pula pemetaan batimetri dan sebaran sedimen permukaan dasar laut. Dua buah contoh sedimen mewakili kedalaman 17-30 cm dan 190-210 cm di bawah dasar laut memeperlihatkan umur 11,54 dan 22,45 tahun. Kecepatan sedimentasi rata-rata 2,03 cm/tahun (pada kedalaman 0-0,3 meter di bawah permukaan dasar laut) dan 8,9 cm/tahun (hingga kedalaman 2,1 meter di bawah dasar laut). Hasil tersebut menunjukkan penurunan kecepatan sedimentasi ke arah atas, yang mengindikasikan bahwa pada saat ini gelombang dan arus kurang berpengaruh terhadap proses sedimentasi. Kata kunci : isotop 210Pb, kecepatan sedimentasi, Tanjung Api-Api